METODE PERHITUNGAN DAN PENGUKURAN ARAH KIBLAT MASJID DI KOTA MATARAM - Jihad, Salimul (LP2M IAIN Mataram, 2012)
Qibla is the compulsory direction for a Muslim to face when praying. However, due to the distance and different places, it often raises the issues of Qibla direction, among which is the issue of accuracy of Qiblah direction actually facing Baitullah al-Haram, including the direction of Qibla mosque in the city of Mataram. With the help of science and technology, particularly science of Falak, the Kaaba as the Qiblah direction can be detected accurately by using careful calculation and measurement which fits well with the principles of science of Falak. Based on the descriptive-analytical study, the qualitative design, it was found out that almost 90% of mosques taken as the sample shows that the direction of mosques in Mataram is in the direction of the Qibla, althought some are not accurate, it still within acceptable limits, i.e. below five degrees difference. Yet remeasurement is still necessary to increase the accuracy and reliabilility, according to the method of measurement and calculation of the direction of the Qibla in Science of Falak.